Assessment of Tractable Cysteines for Covalent Targeting by Screening Covalent Fragments. (9th November 2020) - Petri, László; Ábrányi‐Balogh, Péter; Tímea, Imre; Pálfy, Gyula; Perczel, András; Knez, Damijan; Hrast, Martina; Gobec, Martina; Sosič, Izidor; Nyíri, Kinga; Vértessy, Beáta G.; Jänsch, Niklas; et al.
Abstract: Targeted covalent inhibition and the use of irreversible chemical probes are important strategies in chemical biology and drug discovery. To date, the availability and reactivity of cysteine residues amenable for covalent targeting have been evaluated by proteomic and computational tools. Herein, we present a toolbox of fragments containing a 3, 5‐bis(trifluoromethyl)phenyl core that was equipped with chemically diverse electrophilic warheads showing a range of reactivities. We characterized the library members for their reactivity, aqueous stability and specificity for nucleophilic amino acids. By screening this library against a set of enzymes amenable for covalent inhibition, we showed that this approach experimentally characterized the accessibility and reactivity of targeted cysteines. Interesting covalent fragment hits were obtained for all investigated cysteine‐containing enzymes. Abstract : A toolbox of covalent fragments containing chemically diverse electrophilic warheads is presented. By screening this library against a set of enzymes amenable for covalent inhibition, we experimentally characterized the accessibility and reactivity of targeted cysteines. We propose this approach be used as an experimental method for warhead selection in the development of targeted covalent inhibitors or irreversible probes.